Current status of diagnosis and treatment of primary benign cardiac tumors in children - Sheng, Chuqiao; Yang, Chunfeng; Cheng, Yongkang; Li, Yu-Mei (Frontiers in Cardiovascular Medicine, 2022)
Primary cardiac tumors in children are exceedingly rare overall, which benign accounts for the most part. The onset of the disease is occult, while the clinical manifestations are nonspecific-patients may be asymptomatic or show a range of obstructive, arrhythmic, embolic, or systemic symptoms. The clinical presentations generally depend on the tumor’s size, localization, and pace of growth of the tumor. Moreover, the diagnosis needs comprehensive judgment based on imaging results and pathological examination. With advances in cardiac imagining and the introduction of cardiopulmonary support, the diagnosis and treatment of these rare tumors have improved the prognosis and outlook for benign tumors. To sum up the above, we sought to integrate articles from recent years for the latest comprehensive review of the clinical manifestations, imaging characteristics, clinic pathologic features, and treatment of benign cardiac tumors in children to provide a broader idea for pediatricians to recognize and treat such diseases.